ASPEK LEGALITAS PEDAGANG KAKI LIMA DI KAWASAN WISATA MALIOBORO - Novarisa Permatasari (Fakultas Hukum Universitas Tulang Bawang, 2021)
The purpose of the research to determine the legality aspects of street vendors in the Malioboro tourist area and to analyze the applicable legal sanctions for violators of the rules for good area governance. Street vendors carry out their business to support the economy in fulfilling their daily needs, but there is a need for the realization of an arrangement of regional spatial functions that takes into account all aspects optimally. The Yogyakarta City Government has made a policy in terms of structuring street vendors in order to create a good spatial plan in the Malioboro area. The data collection method in this research is juridical normative by examining secondary data. The results of the study concluded that the street vendors in the Malioboro area can be recognized if they already have a Location Use Permit and have an Identity Card based on the location and provisions on the type of goods. The prohibition for street vendors trading in the Malioboro area is regulated in a Yogyakarta Mayor Regulation and a Yogyakarta City Regional Regulation. Violators of the rules can be subject to criminal sanctions and administrative sanctions as stated in the regulation.